Magnetic iron-oxide nanoparticles in the brain connected to alcohol-associated liver disease - Leon Kaub; Stefan Milz; Nirav Barapatre; Andreas Büttner; Bernhard Michalke; Christoph Schmitz; Stuart A. Gilder (Scientific Reports)
Abstract Magnetic iron-oxide nanoparticles in the form of magnetite (Fe3O4) are present in the human brain. They have been hypothesized to biomineralize in situ, as a result of dysfunctional iron homeostasis related to Alzheimer’s disease, or to enter the brain as airborne pollution particles. Regardless of their origin, magnetic iron-oxides pose a potential hazard to human health due to their high redox activity and surface charge. Here we report measurements on four post-mortem human brainstems, with one brainstem showing approximately 100 times higher magnetite concentrations than the other cases. This brainstem came from a subject with alcohol-associated liver disease (ALD) that manifested in liver cirrhosis and massive hepatic iron overload. Laser ablation – inductively coupled plasma – mass spectrometry showed the highest levels of trace metals (iron, copper and manganese) in the ALD brainstem. It is well established that a dysfunctional liver can result in the accumulation of trace metals in the brain. Our data indicate a similar pathway for magnetite particles, yet liver pathology has not been linked to magnetite occurrence in the brain so far. It may prove to be a crucial factor in understanding the high variation of magnetite concentrations found in human brains.